СТАТИИ ОД МАКЕДОНСКИ АВТОРКИ ОД XIX ВЕК ЗА УЧЕБНОТО ДЕЛО И ЗА ЖЕНСКОТО ПРАШАЊЕ - Славчо Ковилоски (Институт за македонска литература, 2017)
In this study, we present our findings from our research on Macedonian women authors from the XIX century who left original writings on the pages of periodicals. Most of the newspaper articles were written by Slavka Dinkova; however, we also take into account M. H. Zrneva, Evtimica Jancheva, Sultana Chikmakova, Ekaterina and Elena Dukova. Most of the articles of these authors refer to the demands for the education of women, as an unalienable right, whereas others dealt with the male-female relations in Macedonia in that period, too.
Keywords: articles, newspapers, Slavka Dinkova, Sultana Chikmakova, M. H. Zrneva, Evtimica Jancheva, women’s education